The expansion of the sugarcane in the hydrographic basin from Rio Brilhante, Mato Grosso do Sul state: the use of NDVI technique as an instrument for evidencing territorial dynamics - Ferreira, Patricia Silva; Silva, Charlei Aparecido da [UNESP] (Univ Federal Espirito Santo, 2017)
SaThe areas of sugarcane cultivation have expanding, often at the expense of the agricultural and pasture areas. Under this perspective, this manuscript aims to present a methodological guide in order to identify and to map up the areas of sugarcane cultivation, whose unity of analysis was located in the surrounding area of the Rio Brilhante hydrographic basin. We aimed to identify the changes through TM-Landsat5 and OLI-Landsat8 satellite pictures by comparing the scenarios from the years of 2001 and 2015, respectively. The classification of the vegetation was made through the technique of Normalized Difference Vegetation Index (NDVI). Thus, this study points that the use of some techniques and remote sensing tools, like NDVI, when used together with the field research, are extremely efficient for identifying the areas of the sugarcane cultivation.
Keywords: cropland; remote sensing; land use change